Society's Perspective on Career Women - Hamin, Hamidah; Tutdin, Zakia (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
The increase in education also has an impact on the condition of women today, who are no longer dominant in their domestic corner. However, they have expanded into the job market. One of them works as a lecturer. The purpose of this study is to explain the community's view of women who work as lecturers. This research method uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. This research was conducted at Cut Nyak Dhien University of Science. The research subjects were three (3) lecturers at Cut Nyak Dhien University of Science. The results showed that the community's perception of the lecturer profession is very positive, especially since the community has its own pride in women who choose to become teachers. Because according to the community, the job of educating is a very noble profession.